Two-stage melting of au-pd nanoparticles - Mejía Rosales, Sergio; Fernández Navarro, Carlos Javier; Pérez Tijerina, Eduardo Gerardo; Montejano Carrizales, Juan Martín; Yacamán, Miguel José (American Chemical Society, 2006)
Several series of molecular dynamics runs were performed to simulate the melting transition of bimetallic cuboctahedral nanoparticles of gold-palladium at different relative concentrations to study their structural properties before, in, and after the transition. The simulations were made in the canonical ensemble, each series covering a range of temperatures from 300 to 980 K, using the Rafii-Tabar version of the Sutton and Chen interatomic potential for metallic alloys. We found that the melting transition temperature has a strong dependence on the relative concentrations of the atomic species. We also found that, previous to the melting transition, the outer layer of the nanoparticle gets disordered in what can be thought as a premelting stage, where Au atoms near the surface migrate to the surface and remain there after the particle melts as a whole. The melting of the surface below Tm is consistent with studies of the interaction of a TEM electron beam with Au and Au-Pd nanoparticles.